Pengaruh Buzzer di Media Sosial terhadap Pembentukan Opini Publik dalam Pilpres 2024 - Mangido Nainggolan; Ansari Piliang; Dorlian Silalahi; Rizki Jelita Ulandari; Samuel Kevin Armanto Girsang; Shintia Mayda Silitonga (Departement of Mathematics Education, 2024)
Buzzer is no idely knon by the public. The existence of buzzer ith all the pros that he has turned into a phenomenon in his homeland. This is a result of the massive use of social media platforms by various groups. As the function of the buzzer expands and shifts, initially only as an individual ho markets goods or services, then plays a part in the political controversy of the homeland, then many things are influenced by its existence. One is the tendency of the buzzer to be used as a poer tool in an attempt to influence and change public opinion for a specific purpose. Based on these issues, this study aims to dig into ho the role of buzzer in the process of forming public opinion about politics in social media. This research is done using qualitative research methods through case studies approaches. hile in content management, narrative or issues, buzzer doesn't ork alone. But have a hierarchy of ork ith functions and duties respectively. Then in identifying the existence of the buzzer must be seen isely and accurately. Because the ork of the buzzer does not necessarily exist, but it is also not free from the interests and exploitation of certain parties.